GAMBARAN KONSUMSI PANGAN DAN STATUS GIZI ANAK JALANAN DI KOTA MEDAN TAHUN 2014 - ADRY RIDHWANAH; Zulhaida Lubis; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACTStreet children are one of the groups in the community at risk of malnutrition. That is because the diet of street children are generally inadequate and irregular. The purpose of the study was to determine food consumption and nutritional status of street children in the city of Medan in 2014.This research is a descriptive survey. Samples were street children as many as 78 people. The food consumption data types and frequencies were obtained using a food frequency form, while the adequacy of energy and protein was obtained using a 24-hour food recall. Using weighing scales underfoot, and height measurements using microtois. The data collected were analyzed descriptively and presented in the form of a frequency distribution table.The result of this study showed that most street children have normal nutrition, but there are also who have thin nutritional problems. Malnutrition most aged 15-18 years (25.0%). By gender, nutritional status at most malnutrition men (19.1%). Job begging (25.0%) and income < Rp. 7,000 / day (9.1%) had more lean nutritional status. Most street children are sufficient levels of severe energy deficit levels have malnutrition (66.3%). While street children are normal levels of energy sufficiency, the majority of normal nutritional status (91.3%), and some even obese (8.7%). Malnutrition of street children are found in the protein sufficient levels of moderate deficit (28.6% lean), while street children with normal levels of protein adequacy (91.7%) and mild deficits (95.5%) had a majority of nutritional status normal.It is suggested to for the Department of Social and Health Service provide the socialization of health services to street children so that they know and understand about health services and special government programs in health services. Keywords: Food Consumption, Nutritional Status, Street Children